Breakfast Intake and its Association with Body Mass Index among Pre-schoolers in Taska Permata Keluarga Kuala Nerus, Terengganu - Hasmiza, Halib; Wee, Bee Suan; Ong, Ying Qian (2018)
In Malaysia, breakfast is the most frequently skipped meal. Skipping breakfast has been associated with an increased risk of childhood obesity. However, this relationship has not been investigated widely among preschoolers in Malaysia. Hence, this cross-sectional study aimed to determine the association between breakfast intake and Body Mass Index (BMI) among preschoolers in Taska Permata Keluarga (TPK), Kuala Nerus. A total of 131 Malays preschoolers aged four to six years old were recruited from nine TPK using convenience sampling method. Information on sociodemographic, breakfast intake pattern and anthropometric measurements (weight and height) were obtained. Respondents consisted of 74 (56.5%) boys and 57 (43.5%) girls. Anthropometric results showed that 8.4% preschoolers were overweight and obese. Among the preschoolers, 22.1% of them were breakfast skippers. In terms of gender breakdown, 20.3% boys and 24.6% girls skipped breakfast. There was a significant association between breakfast intake and BMI status among preschoolers (p = 0.003). This indicated that preschoolers that skipped breakfast were associated with overweight or obese compared to those who consumed breakfast daily. Breakfast consumption is a marker of a healthy lifestyle which can reduce the risk of childhood obesity. This habit should be inculcated during this critical period of life in which parents play a vital role in promoting breakfast consumption among preschoolers.